Teaching techniques for genes, DNA, and chromosomes: An inventory of 12th-grade high school practice in Pontianak - Muftifah, Khusnun Nisa; Yuniarti, Anisyah; Candramila, Wolly (Universitas Wiralodra, 2025)
Genetic concepts are complex and often lead to student misconceptions due to difficult textbooks and ineffective teaching strategies. Widespread misunderstandings highlight the need for effective instructional techniques to enhance comprehension. This study examine the teaching techniques employed by Biology teachers in 20 high schools in Pontianak City to evaluate their implementation, strengths, and limitations in genetics instruction. This study used a qualitative survey approach to examine teaching techniques for genes, DNA, and chromosomes in 12th-grade classes across 20 high schools in Pontianak City. Data were collected through validated questionnaires and observation sheets, focusing on learning activities, instructional approaches, and challenges faced by teachers. Responses were summarized in tables, analyzed descriptively, and presented to highlight technique variations, selection criteria, and implementation. A total of 20 teaching techniques were identified, with most schools using a combination of 2 to 5 methods, while only three schools applied a single technique, and discussion was the most frequently integrated approach. Teaching techniques for Genes, DNA, and Chromosomes in Pontianak high schools vary, with most teachers combining multiple methods to enhance understanding, interaction, and engagement. The selection and combination of techniques are influenced by student needs, classroom conditions, and learning objectives, highlighting the importance of a balanced approach between student-centered, teacher-led, and objective-driven strategies.